Low-dose aspirin for the prevention of preterm delivery in nulliparous women with a singleton pregnancy (ASPIRIN): a randomised, double-blind, placebo-controlled trial. Issue 10220 (25th January 2020) - Hoffman, Matthew K; Goudar, Shivaprasad S; Kodkany, Bhalachandra S; Metgud, Mrityunjay; Somannavar, Manjunath; Okitawutshu, Jean; Lokangaka, Adrien; Tshefu, Antoinette; Bose, Carl L; Mwapule, Abigail; Mwenechanya, Musaku; Chomba, Elwyn; et al.
Summary: Background: Preterm birth remains a common cause of neonatal mortality, with a disproportionately high burden in low-income and middle-income countries. Meta-analyses of low-dose aspirin to prevent pre-eclampsia suggest that the incidence of preterm birth might also be decreased, particularly if initiated before 16 weeks of gestation. Methods: ASPIRIN was a randomised, multicountry, double-masked, placebo-controlled trial of low-dose aspirin (81 mg daily) initiated between 6 weeks and 0 days of pregnancy, and 13 weeks and 6 days of pregnancy, in nulliparous women with an ultrasound confirming gestational age and a singleton viable pregnancy. Participants were enrolled at seven community sites in six countries (two sites in India and one site each in the Democratic Republic of the Congo, Guatemala, Kenya, Pakistan, and Zambia). Participants were randomly assigned (1:1, stratified by site) to receive aspirin or placebo tablets of identical appearance, via a sequence generated centrally by the data coordinating centre at Research Triangle Institute International (Research Triangle Park, NC, USA). Treatment was masked to research staff, health providers, and patients, and continued until 36 weeks and 7 days of gestation or delivery. The primary outcome of incidence of preterm birth, defined as the number of deliveries before 37 weeks' gestational age, was analysed in randomly assigned women with pregnancy outcomes at or after 20 weeks, according to a modified intention-to-treat (mITT) protocol. Analyses of our binary primary outcome involved a Cochran-Mantel-Haenszel test stratified by site, and generalised linear models to obtain relative risk (RR) estimates and associated confidence intervals. Serious adverse events were assessed in all women who received at least one dose of drug or placebo. This study is registered with ClinicalTrials.gov, NCT02409680, and the Clinical Trial Registry-India, CTRI/2016/05/006970. Findings: From March 23, 2016 to June 30, 2018, 14 361 women were screened for inclusion and 11 976 women aged 14–40 years were randomly assigned to receive low-dose aspirin (5990 women) or placebo (5986 women). 5780 women in the aspirin group and 5764 in the placebo group were evaluable for the primary outcome. Preterm birth before 37 weeks occurred in 668 (11·6%) of the women who took aspirin and 754 (13·1%) of those who took placebo (RR 0·89 [95% CI 0·81 to 0·98], p=0·012). In women taking aspirin, we also observed significant reductions in perinatal mortality (0·86 [0·73–1·00], p=0·048), fetal loss (infant death after 16 weeks' gestation and before 7 days post partum; 0·86 [0·74–1·00], p=0·039), early preterm delivery (<34 weeks; 0·75 [0·61–0·93], p=0·039), and the incidence of women who delivered before 34 weeks with hypertensive disorders of pregnancy (0·38 [0·17–0·85], p=0·015). Other adverse maternal and neonatal events were similar between the two groups. Interpretation: In populations of nulliparous women with singleton pregnancies from low-income and middle-income countries, low-dose aspirin initiated between 6 weeks and 0 days of gestation and 13 weeks and 6 days of gestation resulted in a reduced incidence of preterm delivery before 37 weeks, and reduced perinatal mortality. Funding: Eunice Kennedy Shriver National Institute of Child Health and Human Development.